1996
DOI: 10.1016/0165-7836(96)00473-0
|View full text |Cite
|
Sign up to set email alerts
|

Importance of fish aggregating devices (FADs) as substrates for food organisms of fish

Abstract: Various hypothesis have been proposed to explain why floating artificial habitats are successful in attracting fishes. Food may be a stimulus for aggregating some species around Fish Aggregating Devices (FADs). This study attempts to discover if sessile marine organisms which readily encrust traditional FADs, are important food organisms for fish. A new group of FADs was installed in a rich fishing ground. Different parts of the FADs were sampled every 2 weeks for identification of encrusted organisms, and ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 10 publications
1
15
0
1
Order By: Relevance
“…3), which is consistent with previous conclusions (Kojima, 1967;Hunter and Mitchell, 1968;Ibrahim et al, 1996). Deudero (2001) also suggested that the floating structures probably enhance food availability for associated planktivores but did not identify the possible contributory factors involved.…”
Section: Discussionsupporting
confidence: 89%
“…3), which is consistent with previous conclusions (Kojima, 1967;Hunter and Mitchell, 1968;Ibrahim et al, 1996). Deudero (2001) also suggested that the floating structures probably enhance food availability for associated planktivores but did not identify the possible contributory factors involved.…”
Section: Discussionsupporting
confidence: 89%
“…For example, one study found that L. pacifica was excluded from nearshore kelp forests by the fish Oxyjulis californica , but was able to inhabit floating kelp paddies in high densities when O. californica was absent (Bernstein & Jung, 1979). Studies of the diets of fishes associated with Fish Aggregating Devices (FADs) have found that fishes associated with floating objects rarely feed directly on the fouling community (Ibrahim et al, 1996; Nelson, 2003; Vassilopoulou et al, 2004). The likelihood of predators ingesting plastic by feeding on barnacles may therefore be relatively low.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have studied the fish assemblages associated with FADs and several hypotheses have been put forward to explain the mechanisms regulating fish aggregations and their relationship to the characteristics of FADs (Brock, 1985;Druce and Kingsford, 1995;Helfman, 1981;Ibrahim, 1996;Massutí and Reñones, 1994;Rountree, 1989Rountree, , 1990. Although there is now a better understanding of FAD associations, it is still no easy task to identify the correlations in such a complex phenomenon which involves both biological interactions between species and physical interactions between species and FAD.…”
Section: Discussionmentioning
confidence: 99%